IMPROVING THE QUALITY OF TEACHERS’ TEACHING ADMINISRASTION PLANS THROUGH ACADEMIC SUPERVISING AT SMA IN KABUPATEN ROKAN HULU, RIAU PROVINCE - Parman Hasibuan (English Study Program University of Pasir Pengaraian, 2019)
The research was aimed at improving the teachers’ competence in managing their teaching administration effectively. At the beginning, it was found that majority of English teachers in SMA did not have complete the components of teaching Administration as suggested by the educational ministry regulation number 41/2007 in Kurikulum Tingkat Satuan Pendidikan (KTSP). It was because almost all English teachers did not know what they should prepare for their administration fulfillment. The research is a case study. The data collection of the study was gained through the activities of pre-observation, field notes, real observation, colleague coaching or training, and documentation. Those data were then analyzed using table of scores in the professional competence instrument. The steps taken to overcome the teachers’ teaching administration problems are among others by doing some strategies of coaching, guiding, discussing and socializing the standardized process of Indonesian National Standard of Education to English teachers. As a result of the study, from almost zero to hero, the teachers’ understanding and competences aboutteaching administration fulfillment raised, ranging from 29% to 87% (at the beginning to the end of the study). School supervisors are recommended to do similar research activities to prove the truth of the findings. For teachers, particularly English teachers, it is suggested that they change their mind set in managing their jobs. Finally, it is expected that this study will have good contribution to enhance the English teachers’ competences in managing their jobs.